COVID-19 and pathways to low-carbon air transport until 2050. (9th March 2021) - Gössling, Stefan; Humpe, Andreas; Fichert, Frank; Creutzig, Felix
Abstract: The COVID-19 pandemic has led to an unprecedented decline in global air transport and associated reduction in CO2 emissions. The International Civil Aviation Organization (ICAO) reacted by weakening its own CO2 -offsetting rules. Here we investigate whether the pandemic can be an opportunity to bring the sector on a reliable low-carbon trajectory, with a starting point in the observed reduction in air transport demand. We model a COVID-19 recovery based on a feed-in quota for non-biogenic synthetic fuels that will decarbonize fuels by 2050, as well as a carbon price to account for negative externalities and as an incentive to increase fuel efficiency. Results suggest that until 2050, air transport demand will continue to grow, albeit slower than in ICAO's recovery scenarios, exceeding 2018 demand by 3.7–10.3 trillion RPK. Results show that synthetic fuels, produced by 14–20 EJ of photovoltaic energy, would make it possible to completely phase out fossil fuels and to avoid emissions of up to 26.5 Gt CO2 over the period 2022–2050.